The Indian Removal Act and the Trail of Tears - Hamen, Susan E. (Building our nation., 2020)
Describes the expansion of the United States, focusing on the settlers' conflicts with American Indian nations. Discusses broken treaties, acculturation, the work of U.S. Presidents Thomas Jefferson and Andrew Jackson, the Indian Removal Act, and the Trail of Tears. Includes a quiz with answer key, a glossary, color illustrations, and further resources.